THE ROLE OF SCIENTIFIC RESEARCH WORK IN THE DEVELOPMENT OF MUSIC EDUCATION EDUCATION - Madaminov Nasimjon Xoljurayevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Human upbringing, maturation, has been one of the most pressing problems of any society. Because the formation, development, prosperity of society depends on its upbringing in this society. Upbringing is a continuous process that consists in regularly influencing the spiritual and physical development of a person in order to prepare him for a relationship of social economic production. Therefore, educating young people is an important example, mobilizing them on the way to improve our independence. In our independent republic, issues of spirituality and culture are paid attention to, intensive work has been carried out in the field of music education. Music schools arose. Technical and educational institutes, technical knowledge institutions were established. Children's music schools, student palaces, amateur clubs teachers ' training and re-education institutes scientific examination institutes were opened. Serious restructuring of the music education system took place.